Understanding luxury consumption drivers - Lefkeli, Deniz (My University, 2017)
Bu çalışmada materyalizmin, kozmopolitliğin, gösterişin, özgün olma ihtiyacının, özbenlik kurgusunun ve gelecekteki benliğe olan bağlılığın satın alma niyetini nasıl etkilediği incelenmiştir.

In this study, the way in which materialism, cosmopolitanism, vanity, need for uniqueness, self-construal, and future-self continuity impact purchase intention is examined.
Keywords: İşletme; lüks tüketim luxury consumption; Pazarlama; Üretim; Yönetim